Designs balanced for neighbor effects in circular binary blocks of size ten - Rashid Ahmed; Munir Akhtar; Farrukh Shehzad (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2011)
Neighbor balanced designs are more useful to remove the neighbor effects in experiments where the performance of a treatment is affected by the treatments applied to its adjacent plots. These designs ensure that treatment comparisons will be less affected by neighbor effects as possible. In literature, these designs are available in circular blocks of size 3, 5, 6, 8, 9. In this article, neighbor balanced designs are constructed in circular binary blocks of size ten. A catalogue of these designs is also compiled.
Keywords: 330; Binary blocks; Circular blocks; Neighbor effects; Neighbor balanced designs